Electroencephalographic Abnormalities in Children with Attention Deficit Hyperactivity Disorder without Known Epilepsy – A cross sectional study - Paul, Bikush Chandra; Islam , Kazi Ashraful; Ahmed, Sanjida; Nabi, Naheed; Mukib, ABM; Liza, Noor A Sabah; Fatema, Kanij; Alam, Sydea Tabassum; Kundu, Gopen Kumar; Akhter, Shaheen (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Attention deficit hyperactivity disorder (ADHD) is a common problem in the field of Pediatric neurology and psychiatry, often accompanied by various comorbidities such as epilepsy. Electroencephalography (EEG) abnormalities are frequently observed in a certain proportion of ADHD cases. This study aimed to observe the EEG abnormalities in children with ADHD without known epilepsy. Materials and Methods: A cross-sectional study was carried out at the Institute of Pediatric Neurodisorder and Autism (IPNA), Bangabandhu Sheikh Mujib Medical University (BSMMU) over a 12-month period from July 2020 to June 2022. Participants included children aged 3-15 years diagnosed with ADHD based on DSM-5 criteria. Individuals with neurodegenerative disorders, epilepsy, visual or hearing impairments, cerebral palsy, or other neurobehavioral disorders were excluded. Ethical clearance was obtained from the Institutional Review Board (IRB) of BSMMU prior to the study, and written consent was obtained from parents/caregivers. EEG evaluations were conducted on all participants over a 30-minute period, encompassing both sleep and wakefulness, with activation procedures during recording. Results: Seventy children diagnosed with ADHD were enrolled, with a mean age of 7.41±2.86 years and a male-to-female ratio of 4:1. ADHD sub types included primarily inattentive (8.6%), primarily hyperactive/impulsive (28.6%), and combined type (62.9%). Normal EEG recordings were observed in 60% of children, while abnormal recordings were found in 40% of cases. Among those with abnormal EEG findings, 3.6% were primarily inattentive, 39.3% were primarily hyperactive/impulsive, and 57.1% were of the combined type. Generalized epileptiform discharges were present in 14.3% of children, and focal epileptiform discharges in 20%. Conclusion: The study concluded that abnormal EEG findings were prevalent in children with ADHD even in the absence of clinical seizures or epilepsy. EEG evaluation should be considered for the proper management of children with ADHD. J Bangladesh Coll Phys Surg 2025; 43: 46-52